2019
DOI: 10.1145/3368426
|View full text |Cite
|
Sign up to set email alerts
|

Blind Leading the Sighted

Abstract: Voice-activated personal assistants (VAPAs) are becoming smaller, cheaper, and more accurate, such that they are now prevalent in homes (e.g., Amazon Echo, Sonos One) and on mobile devices (e.g., Google Assistant, Apple Siri) around the world. VAPAs offer considerable potential to individuals who are blind, offering efficiencies over gesture-based input on touchscreen devices. However, research is just beginning to reveal the ways in which these technologies are used by people who are blind. In the first of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…These results support those found in other research on: the use of advanced learning technologies in the LMS as a good resource for learning regulation [13]; the use of advanced technologies in LMS learning with personalized attention [2,12,14]; the use of PBL in LMS environments for increasing collaborative work [6,7]; and the use of LMS with additional technologies, which, together with a pedagogical model similar to the one applied in this study [15], increased the motivation and the effectiveness of learning among students [3]. In addition, specifically in the group with access to an IPA, greater satisfaction was found with the teaching-learning process [22], with teacher guidance in the teaching-learning process [23,24], and greater general satisfaction [44].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These results support those found in other research on: the use of advanced learning technologies in the LMS as a good resource for learning regulation [13]; the use of advanced technologies in LMS learning with personalized attention [2,12,14]; the use of PBL in LMS environments for increasing collaborative work [6,7]; and the use of LMS with additional technologies, which, together with a pedagogical model similar to the one applied in this study [15], increased the motivation and the effectiveness of learning among students [3]. In addition, specifically in the group with access to an IPA, greater satisfaction was found with the teaching-learning process [22], with teacher guidance in the teaching-learning process [23,24], and greater general satisfaction [44].…”
Section: Discussionmentioning
confidence: 80%
“…Regarding the studies on the usability assessment of IPAs, users have indicated that interfaces must be adapted to the needs of each task [23,24]. IPAs that include holograms are under evaluation as learning aids [25,26].…”
Section: Advanced Learning Technologies and Intelligent Personal Assimentioning
confidence: 99%
“…In addition, VAs leverage speech-based interaction, which makes information lookup more efficient and accessible compared to classical methods (eg, desktop web search [11,12]). This is particularly the case in situations in which users have their hands occupied [13][14][15][16][17], lack reading and writing skills [18], or suffer from visual, motor, or cognitive inabilities [19][20][21][22][23][24] and cannot access information on display devices, such as smartphones, desktops, or tablets. Hence, VAs are a powerful alternative to provide chronic patients with easy access to information about NCD management.…”
Section: Voice Assistants For Information Lookupmentioning
confidence: 99%
“…This may reflect a tendency to transfer the responsibility of information retrieval to the patients, whereas they are in charge of choosing (the most) reliable information source. As we believe in the potential of VAs in increasing the accessibility of health information by vocally interacting with patients having their hands occupied or with disabilities [13][14][15][16][17][19][20][21][22][23][24], we urge Apple to consider favoring voice responses over lists of results to make the information search more suitable for hands-free interaction.…”
Section: Response Rate Across Developers and Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation